A ketone monoester drink reduces the glycemic response to an oral glucose challenge in individuals with obesity: a randomized trial - Myette-Côté, Étienne (Am J Clin Nutr, 2019)
BACKGROUND: Exogenous ketones make it possible to reach a state of ketosis that may improve metabolic control in humans. OBJECTIVES: The main objective of this study was to determine whether the ingestion of a ketone monoester (KE) drink before a 2-h oral-glucose-tolerance test (OGTT) would lower blood glucose concentrations. Secondary objectives were to determine the impact of KE on nonesterified fatty acid (NEFA) concentration and glucoregulatory hormones. METHODS: We conducted a randomized controlled crossover experiment in 15 individuals with obesity (mean ± SD age: 47 ± 10 y; BMI: 34 ± 5 kg/m(2)). After an overnight fast, participants consumed a KE drink [(R)-3-hydroxybutyl (R)-3-hydroxybutyrate; 0.45 mL/kg body weight] or taste-matched control drink 30 min before completing a 75-g OGTT. Participants and study personnel performing laboratory analyses were blinded to each condition. RESULTS: The KE increased d-β-hydroxybutyrate to a maximum of ∼3.4 mM (P < 0.001) during the OGTT. Compared with the control drink, KE reduced glucose (−11%, P = 0.002), NEFA (−21%, P = 0.009), and glucagon-like peptide 1 (−31%, P = 0.001) areas under the curve (AUCs), whereas glucagon AUC increased (+11%, P = 0.030). No differences in triglyceride, C-peptide, and insulin AUCs were observed after the KE drink. Mean arterial blood pressure decreased and heart rate increased after the KE drink (both P < 0.01). CONCLUSIONS: A KE drink consumed before an OGTT lowered glucose and NEFA AUCs with no increase in circulating insulin. Our results suggest that a single drink of KE may acutely improve metabolic control in individuals with obesity. Future research is warranted to examine whether KE could be used safely to have longer-term effects on metabolic control. This trial was registered at clinicaltrials.gov as NCT03461068.